Pengaruh Persepsi, Gender dan Lingkungan Kerja terhadap Pemilihan Karir Mahasiswa Akuntansi sebagai Akuntan Publik - Stella Mutiara; Suyatmin Waskito Adi (LPPM IAI Nasional Laa Roiba Bogor, 2023)
The public accountant profession will later become one of the interesting and promising job choices for accounting students by relying on high expertise and skills and behaving independently. One of the accountant professions that is very popular in society and especially among accounting students is the Public Accountant Profession. With the wide range of job opportunities as an accountant, it should be able to attract students to a career as an accountant, considering that the profession is very important and so needed. The purpose of this study was to analyze the effect of perceptions, gender and work environment on accounting students' career choices as public accountants. This research uses quantitative methods. The population used in the study was accounting study programs at UMS and UNS class of 2019/2020. Sampling using the Purposive Sampling method with the criteria of Accounting Students in the Class of 2019 and 2020 at Universitas Muhammadiyah Surakarta and Sebelas Maret University who have received auditing courses, then a sample of 110 respondents was obtained. The data used in this study are primary data collected and processed by themselves, the results of which are in the form of numbers listed on the questionnaire scale which are processed using the SPSS program. The technique used in data collection is the questionnaire / questionnaire media. The technique used in data collection is a questionnaire. The data analysis technique used is multiple linear regression analysis. The results of the t test show that the Perception and Gender variables have a positive effect on students' decisions to choose a career in public accounting. Meanwhile, the work environment variable has no effect on students' decisions to choose a career in public accounting.